Hesitating Between Irony and the Desire to be Serious in Moi, Tituba, sorcière... noire de Salem: Maryse Condé and her Readers - Sarah E. Barbour (Studies in 20th & 21st Century Literature, 2004)
In writing her fifth novel, a fictive autobiography of the title character, Maryse Condé has said that she "felt a strong solidarity with Tituba," and at the same time she admits hesitating "between irony and a desire to be serious" in the invention of this "mock-epic character." This article explores the reader's relationship to the novel as a variation on this hesitation. Once Condé sets up Tituba's authority to narrate her story, the reader is left in the precarious position of hesitating between getting the author's irony and desiring to be serious about Tituba's narrative of a painful history. By using and effectively abusing the way in which irony has traditionally been seen to create a hierarchy of those who get it and those who do not, Condé moves her readers in and out of a stable position in relation to Tituba's narrative, inviting us to think more critically about how we read Tituba back into history.
Keywords: Maryse Condé; Tituba; solidarity; irony; mock-epic character; reader& #x27; s relationship; reader; hesitation; authority; hierarchy; Tituba& #x27; s narrative; & quot; Moi; Sorciere& quot